Prudential Regulatory and Supervisory Practices for Fintech : Payments, Credit and Deposits - World Bank Group (World Bank, Washington, DC, 2020)
This report is a stock-take of the state of prudential regulation and supervision of fintech. It focuses on prudential questions related to three primary products—transaction accounts (deposits and e-money accounts), credit, and payments. As such, the report covers e-money providers, P2P platforms, and overall outsourcing of the banking sector industry. The report identifies typologies of existing regulatory approaches, as well as emerging questions concerning: monitoring, engagement, and test environments; licensing; supervision; resolution; safety nets; and national and international coordination.